ANALYSIS OF IMMIGRATION AUTOGATE PLACEMENT LAYOUT TO EXPEDITE PASSENGER BOARDING PROCESS AT THE AIRPORT - Roland, Jenov (Journal of Airport Engineering Technology (JAET), 2025)
Ideally, an international terminal should have additional inspection procedures, including immigration, customs, and health checks, while providing excellent service to passengers from various countries. Currently, at Terminal 2 of Juanda International Airport, immigration autogates are only available at gates 6–8, while gates 1–5, which were previously used for domestic flights, are not yet equipped with immigration facilities. This study aims to identify the passenger boarding process and determine the appropriate placement layout for immigration autogates at the former domestic gates in Terminal 2 of Juanda International Airport Surabaya. Using a descriptive qualitative approach, data were collected through observation, interviews with informants, and documentation. Data analysis techniques included data reduction, data presentation, and data verification. The findings indicate that boarding time at gates 1–5 reaches 20 minutes and is not friendly to vulnerable groups. The location of immigration autogates at gates 6–8 prolongs the boarding process and requires shuttle bus services to the aircraft parking area. Ideally, immigration autogates should be placed at the junction in front of gates 1–5, reducing boarding time to 5–10 minutes. In conclusion, the passenger boarding flow at gates 1–5 of Terminal 2 at Juanda International Airport Surabaya is not yet optimal, and immigration autogates should be placed at the junction near the waiting rooms for gates 1–5.